ADAPTASI DOKTRIN PROMISSORY ESTOPPEL DALAM PENYELESAIAN GANTI RUGI PADA TAHAP PRA KONTRAK PADA HUKUM KONTRAK DI INDONESIA - Hadi Susetya, I Gde Prim; Pasek Diantha, I Made; Cakabawa Landra, Putu Tuni (Acta Comitas, 2018)
Pre-contractual phase is an early phase of a negotiation of two-sided affairs. This phase can be also called as the early phase of negotiation or agreement or understanding before enters the actual contract agreement. Legal issues will arise, if before thecontract has not validand bind of the two-sided affairs yet, namely in the negotiation process or preliminary negotiation; one of the two-sided affairs has disobeyed the law legal actions such as borrow money, buy land, however, they have not reached the final agreement yet regarding the negotiated business contract. This case can be occurred because one of the parties obviously trusts and hopes in the promises which are given by another party. If, in the end, the final agreement is deadlocked and has no reached any deal at all, such as the agreement is unreachable regarding of fees, royalties or license terms, any expenses and the investments that has spent by his business partnerwill not be sued for the compensation. Based on these problems, therefore the problems of study that can be appointed are (1) How does to set compensation arrangement setting based on the legal system in Indonesia and (2) How does to adapt the Doctrine of Promissory Estoppel in contract law in Indonesia. Regarding there is no norm that enlisted the effects of law in pre-contractual phase either in the Civil Procedure Code or in any other legislation related to contract law; therefore, this study uses normative legal studies. This study uses a comparative, case studies and conceptual approaches. The sources of legal materials in the study consist of primary legal, secondary and tertiary materials. The collection method of the sources of legal materials is by conducting the library studies. The used analysis methods of legal materials are descriptive, systematic, and evaluative methods. The results of the study indicated that (1) the compensation arrangement setting has not been regulated strictly either in the Civil Procedure Code or in any other legislation related to contract law. In the Civil Procedure Code, the compensation will be given only if wanperstasi (in form of breach of contract) and tort occur. However, if one of the parties feels aggrieved in the pre-contractual phase, it can sue to the District Court. (2) Adapting the legal doctrine of Promissory Estoppel into Indonesian legal system can be conducted because both of the legal system in common law (British and United States of America) and legal system in Indonesia have similarities, so that the courts in Indonesia can use the doctrine to fill the legal vacuum in contract law. Keywords: The Doctrine of Promissory Estoppel, Compensation, Pre-Contractual Phase.